3D Free-standing graphene: influence of etching solution and etching time on chemical vapor deposition on the graphene/nickel foam - Nurul Nabila Rosma,; Rozan Mohamad Yunus,; Nur Rabiatul Adawiyah Mohd Shah,; Khuzaimah Arifin,; Lorna Jeffery Minggu,; Norasikin Ahmad Ludin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Three-dimensional (3D) structures made of graphene sheets have been developed recently, and have resulted in the development of a new class of graphene materials known as 3D graphene materials. High-quality free-standing 3D graphene foam has been synthesized by chemical vapor deposition (CVD) on nickel foam followed by a chemical etching process to remove the nickel foam as a template. Field-emission scanning electron microscopy (FESEM), x-ray diffraction (XRD), and Raman spectroscopy measurements were performed to investigate the morphologies, crystal phase, and the structure of nickel foam (NF), graphene/nickel foam (Gr/NF), and 3D graphene (3D Gr). In this study, the influence of etching solution and etching time on Gr/NF to produce free-standing 3D Gr was investigated. XRD spectroscopy showed that the mixed solutions of 1M FeCl3:1M HCl at 80 °C for 3 h can significantly remove the NF and no peaks of NF are observed, thus indicating a high crystal quality of 3D Gr was obtained. In addition, XRD spectroscopy revealed that by increasing the etching time beyond 3 h, the intensity of diffraction peaks decreases, thus degrading graphene quality. This research emphasizes the significance of proper selections of etching solution and etching time in removing the NF to maintain the characteristic, quality, and surface morphology of 3D Gr after the etching process.